Money and banking in Latin America - Rietti, Mario; Mena, Antonio Ortiz (New York : Praeger Publishers, 1979)
In this book the author gives a systematic account of the monetary, financial, and banking developments that have taken place in the region since the early 1960s. He stresses the noteworthy progress made in expediting financial growth, in mobilizing financial resources, and in strengthening savings and investment in the countries of the region.
Includes bibliographical references: p. 208-214.
rpm 30/04/2018
Loans
Keywords: Financial institutions; Money; Banks and banking